Profil Ternak Ruminansia Potong di Kabupaten Barito Selatan (Ruminant Livestock Profile in South Barito Regency) - Budya Satata; Lisnawaty Silitonga (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2012)
This study aims to determine the development of ruminant livestock, especially cattle, buffaloes and goats over a period of 5 years from 2005 to 2009 and to know development of the farmers who are seeking and maintain of cattle, buffaloes and goats in the district of South Barito. This research is using descriptive method by using data derived from relevant agencies such as Fisheries and Animal Husbandry department of South Barito Regency, Department of Agriculture and Animal Husbandry Central Kalimantan Province and the results of surveys conducted in the study area. The data obtained were analyzed using proportional analysis of individual cases of the observed variables. The results showed an increase in cattle population of 15.16%, 5.93% buffalo and goat by 6.07%. In each year the average number of cows cut as many as 528.2 head, buffaloes 15.6 head and goat 1447.2 head. The average number of cows that came out of the study area as much as 196.6 head/ yr, 118.8 buffalo head / yr and 283 goat head / yr. The average number of cows that entered into the study area as much as 34.4 tails, ox 97.2 tails and goat 347 tails. Whereas the average cow is grown by 11.72 per family tails, ox 27.98 tails and goat 11.08 tails. The average number of cattle per farmer’s family are 5.36 tails, buffalo dan goats are 10.18 tails and 3.52 tails.